Approaches for thoracoabdominal oesophagectomy for oesophageal cancer: a network meta-analysis – study protocol - Ulrich Ronellenfitsch; Juliane Friedrichs; Johannes Vey; Johannes Klose; Maurizio Grilli; Joerg Kleeff; Artur Rebelo; Marie Merling (BMJ Open)
Introduction Oesophageal cancer is the seventh most frequently diagnosed cancer and the sixth leading cause of cancer-related deaths worldwide. Oesophagectomy remains the main curative treatment option. The effect of different surgical approaches (completely open, hybrid, completely minimally invasive and robot-assisted) on patients undergoing thoracoabdominal oesophagectomy (Ivor-Lewis’s procedure) for oesophageal cancer is evaluated, focusing on overall survival, postoperative mortality and morbidity.Methods and analysis A systematic literature search will be conducted in PubMed/Medline, Cochrane Library, Embase, Cumulated Index in Nursing and Allied Health Literature, ClinicalTrials.gov and International Clinical Trials Registry Platform using predefined search terms. A random-effects (network) meta-analysis using the frequentist framework will be performed.Ethics and dissemination As this study is based on previously published data, no ethical approval is required. Findings will be disseminated through peer-reviewed publications and conference presentations to inform clinical decision-makers (eg, surgeons, gastroenterologists).Trail registration number CRD42024564915.